Recommendations for performing measurements of apparent equilibrium constants of enzyme-catalyzed reactions and for reporting the results of these measurements - Goldberg, Robert N.; Giessmann, Robert T.; Halling, Peter J.; Kettner, Carsten; Westerhoff, Hans V. (Beilstein Journal of Organic Chemistry, 2023)
The measurement of values of apparent equilibrium constants K′ for enzyme-catalyzed reactions involve a substantial number of critical details, neglect of which could lead to systematic errors. Here, interferences, impurities in the substances used, and failure to achieve equilibrium are matters of substantial consequence. Careful reporting of results is of great importance if the results are to have archival value. Thus, attention must be paid to the identification of the substances, specification of the reaction(s), the conditions of reaction, the definition of the equilibrium constant(s) and standard states, the use of standard nomenclature, symbols, and units, and uncertainties. This document contains a general discussion of various aspects of these equilibrium measurements as well as STRENDA (Standards for Reporting Enzymology Data) recommendations regarding the measurements and the reporting of results.
Keywords: enzyme-catalyzed reactions; equilibrium constant; standards; thermodynamics